2016
DOI: 10.4103/0971-4065.172227
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glomerular basement membrane crescentic glomerulonephritis: A report from India and review of literature

Abstract: Anti-glomerular basement membrane (anti-GBM) disease is an autoimmune disease that most commonly presents as rapidly progressive glomerulonephritis with or without pulmonary involvement. It is characterized by the presence of antibodies directed to antigenic targets within glomerular and alveolar basement membranes. This study was performed to evaluate the clinicopathological features and outcome in anti-GBM crescentic glomerulonephritis (CrGN) at a tertiary care center in North India over a period of 9 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…Among 9 double-positive patients, 8/9 (88.8%) were p-ANCA positive. In a study by McAdoo et al, patients who are double-positive accounted for 47% of all anti-GBM disease cases, whereas only 23–29% of patients have double positivity in Indian studies [4, 5, 12]. Our study also highlights this common concurrence.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Among 9 double-positive patients, 8/9 (88.8%) were p-ANCA positive. In a study by McAdoo et al, patients who are double-positive accounted for 47% of all anti-GBM disease cases, whereas only 23–29% of patients have double positivity in Indian studies [4, 5, 12]. Our study also highlights this common concurrence.…”
Section: Discussionsupporting
confidence: 60%
“…The principal target of the autoimmune response has been identified as the noncollagenous (NC1) domain of the a3 chain of type-IV collagen (a3[IV]NC1; the “Goodpasture autoantigen”) [3]. It is responsible for 10–20% of rapidly progressive renal failure with a bimodal age of presentation [4, 5]. Patients commonly experience non-specific prodromal symptoms for a few weeks, leading to rapidly progressive glomerulonephritis and pulmonary hemorrhage [2].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In a study from the University of North Carolina Nephropathology Laboratory, patients less than 20 years constituted 11.5% of CrGN. [ 11 ] We found that CrGN is uncommon in children with only 17 (7.9%) pediatric patients at presentation.…”
Section: Discussionmentioning
confidence: 90%
“…[ 3 ] We have previously shown that anti-GBM CrGN has a poor renal outcome with rapid deterioration requiring renal replacement therapy. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%